Accountability as a strategy for resource mobilization in nonprofit organizations (Desenvolvimento em Questão, 2026)
This study sought to analyze the extent to which accountability can enhance the processes and outcomes of resource mobilization in third-sector organizations. It is a qualitative, descriptive study conducted through a multiple case analysis involving two nonprofit institutions and two donors associated with each organization. Data were collected through semi-structured interviews, recorded, transcribed, and submitted to content analysis, complemented by a similarity analysis supported by the IRaMuTeQ software. The results show that systematic accountability practices, such as the use of social media, financial and technical reports, meetings, and feedback events, strengthen transparency, increase institutional credibility, and contribute to donor retention, positively influencing fundraising efforts. Conversely, relevant barriers were identified, such as the shortage of qualified fundraising professionals, the limited internalization of governance mechanisms, and the social prejudice that still associates the third sector solely with charity, disregarding its economic and productive role. It is concluded that strengthening accountability constitutes a central strategy for building trust-based relationships, expanding the donor base, and enhancing the sustainability of the organizations investigated.
Keywords: Accountability; transparency; fundraising; third sector